Optimizing Receptive and Productive Skill Instruction in Arabic Through My Klass: A Digital Case Study of the Ta’bir Syafawi Course - Fitri Zakiyah; Moh. Idris; Abdel Rahman El Sayed Abdel Ghaffar Balah (ALSINATUNA, 2023)
The rapid advancement of digital technologies has significantly transformed educational practices, though their integration into language instruction remains uneven. This study explores the digitization of receptive and productive language skills in the ta’bir syafawi (oral expression) course within the Arabic Education Department at Universitas Muhammadiyah Yogyakarta, Indonesia, focusing on the use of the institutionally mandated My Klass platform. Framed within broader debates on Arabic digital pedagogy, the study focuses on reconfiguring oral skills instruction. Utilizing a qualitative case study approach, data were collected through detailed observation and documentation of My Klass usage, and analyzed following Miles and Huberman’s model—data reduction, data display, and conclusion drawing. Findings indicate that My Klass, a Moodle-based Learning Management System (LMS), supports two central components: instructional activities (attendance, assignments, discussion forums, feedback) and instructional content (uploaded files, hyperlinks). The platform supports flexible, centralized learning that fosters autonomy and enhances linguistic skills. Nonetheless, the study identifies persistent challenges, including lecturers’ limited technological proficiency, decreased learner engagement, social isolation, and concerns about data privacy. The research highlights My Klass’s pedagogical contributions while underscoring the need for sustained institutional support and enhanced technological capacity to optimize its implementation in Arabic language education.